1983
DOI: 10.1007/bf02405126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholecalciferolin vivo on proteins and lipids of skeletal muscle from rachitic chicks

Abstract: The protein and lipid constituents of skeletal muscle subcellular fractions isolated from chicks fed a vitamin D-deficient diet for 3 weeks and chicks replated with cholecalciferol (vitamin D3) were analyzed. Administration of the sterol markedly altered the protein composition of mitochondria. The changes were localized in the inner membranes and consisted of a modification of the relative amounts of proteins of approximate mol wt of 83,000, 58,000, 42,000, and 34,000. In addition, treatment with vitamin D3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…However, administration of the sterol results in a marked alteration of the protein composition of mitochondria. These changes are localized in the inner membranes and consist in a decrease of the relative amounts of proteins of approximate mol wts of 83,000 and 58,000, accompanied by an increase of proteins with approximate mol wts of 42,000 and 34,000 (70). In general agreement with these observations, it has been shown that vitamin D stimulates in vivo [ 3 H]leucine labeling of total mitochondrial proteins (71).…”
Section: Studies In Vivosupporting
confidence: 59%
See 2 more Smart Citations
“…However, administration of the sterol results in a marked alteration of the protein composition of mitochondria. These changes are localized in the inner membranes and consist in a decrease of the relative amounts of proteins of approximate mol wts of 83,000 and 58,000, accompanied by an increase of proteins with approximate mol wts of 42,000 and 34,000 (70). In general agreement with these observations, it has been shown that vitamin D stimulates in vivo [ 3 H]leucine labeling of total mitochondrial proteins (71).…”
Section: Studies In Vivosupporting
confidence: 59%
“…In addition, it has been shown that SR membranes from vitamin D-repleted animals contain higher relative amounts of phospholipid than animals deficient in the sterol. However, no changes in phospholipid composition were detected between both experimental groups (70). The role of the vitamin Ddependent increase in SR phospholipid content in changes in SR Ca transport induced by the sterol is not known.…”
Section: Studies In Vivomentioning
confidence: 81%
See 1 more Smart Citation
“…It is possible that the HiD diet in our study attenuated the disease-induced rapid decline in muscle function and strength by modulating the mechanisms involved in contractile protein synthesis and energy homeostasis. Indeed, vitamin D 3 and/or its metabolites increase troponin C [39], mediate protein synthesis and cellular ATP stores [40], and increase actin and sarcoplasmic protein expression [41] in striated muscle. Vitamin D 3 supplementation above the adequate intake may be a potential therapeutic in disease states involving loss of motor neuron stimuli to voluntary muscles or loss of muscle mass and function due to immobilization, disuse, cachexia, sarcopenia, or neuromuscular disease.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, vitamin D deficiency impairs intracellular calcium kinetics and muscle cell contractility [8,9], mitochondrial metabolism [10,11] and protein synthesis [12,13]. Treatment with vitamin D corrects these impairments [14,30] as well as restoring strength and improving balance in vitamin D deficient humans [16,29,31]. Despite the fact that vitamin D deficiency is associated with muscle loss [12,13] and weakness [16,28,29], which may contribute to the significant muscle atrophy, weakness, and widespread disability experienced by patients with ESRD, the current focus of vitamin D treatment for the control of SHPT, as outlined in the current K/DOQI guidelines [5], is on measuring its effects on bone metabolism and tissue calcification.…”
Section: Discussionmentioning
confidence: 99%